اتجاهات معلمي الصفوف نحو استخدام طريقة المتشابهات (دراسة ميدانية لدى عينة من معلمي الحلقة الأولى من مرحلة التعليم الأساسي في مدارس مدينة اللاذقية) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
هدف البحث إلى تعرّف اتجاهات معلمي الصفوف نحو استخدام طريقة المتشابهات، وتعرّف الفروق في اتجاهاتهم تبعاً لمتغيري الجنس ومدة الخدمة، ولتحقيق هذا الهدف اتبع البحث المنهج الوصفي، وصُممت استبانة مكونة من(35) فقرة موزَعة على محاور (مفهوم طريقة المتشابهات، فوائد طريقة المتشابهات، إمكانية تطبيق طريقة المتشابهات، الاهتمام بطريقة المتشابهات، محاذير استخدام طريقة المتشابهات)، وبعد التأكد من دلالات صدقها وثباتها طُبقت على عينة مكونة من (714) معلماً ومعلمةً من معلمي الصفوف في مدينة اللاذقية، وأشارت النتائج إلى وجود اتجاهات ايجابية لدى معلمي الصفوف نحو استخدام طريقة المتشابهات، كما أظهرت النتائج عدم وجود فروق دالة إحصائياً تُعزى لمتغير الجنس في اتجاهاتهم نحو طريقة المتشابهات ككل وفي كل محور من المحاور على حده، وبينت النتائج عدم وجود فروق دالة إحصائياً في اتجاهاتهم تعزى لمتغير مدة الخدمة بالنسبة للمحاور ككل، وفي كل من محاور ( مفهوم طريقة المتشابهات، فوائد طريقة المتشابهات، محاذير استخدام طريقة المتشابهات) في حين كانت الفروق دالة إحصائياً في اتجاهات المعلمين ذوي الخبرة الأقل والمعلمين ذوي الخبرة الأكثر في كل من محوري (إمكانية تطبيق طريقة المتشابهات، الاهتمام بطريقة المتشابهات). The research aimed to identify  the attitudes of the teachers toward using the similarities method, and  to identify the differences in their attitudes in relation to the gender and experience period variables, and to achieve this purpose the research followed the descriptive approach, and a questionnaire had been designed consisting of (35) items distributed on the axes (the concept of the similarities method, benefits of the similarities method, the possibility of application the similarities method, the interesting in the similarities method, and the warning of using the similarities method), and after confirming from its validity and reliability semantics, the questionnaire had been applied on (714) teachers from Lattakia city' schools, the results indicated that the teachers have positive attitudes toward using the similarities method, and the results showed that there were no statistically significant differences in teachers' attitudes due to the gender variable in relation to the axes as a whole, and in each axis, but the differences were statistically significant between the least experienced teachers and the most experienced teachers in each of  the possibility of application similarities method  and the interesting  in  the similarities method axes in favor of the least experienced teachers.